2013
DOI: 10.5380/ce.v18i3.33564
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento De Mulheres Acerca Do Papilomavírus Humano E Sua Relação Com O Câncer De Colo Uterino

Abstract: RESUMO:Este estudo teve como objetivo verificar o conhecimento de mulheres acerca do papilomavírus humano e sua relação com o câncer de colo uterino, forma de transmissão, prevenção, diagnóstico e tratamento. Trata-se de um estudo exploratório, descritivo de abordagem quantitativa realizado em Centro CONOCIMIENTO DE MUJERES ACERCA DEL PAPILOMA VIRUS HUMANO Y SU RELACIÓN CON EL CÁNCER DE CUELLO DE ÚTERO RESUMEN:Este estudio tuvo el objetivo de verificar el conocimiento de mujeres acerca del papilomavírus human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
4
0
6
Order By: Relevance
“…A study conducted in the city of Teresina/PI with 126 women showed that 71.4% self-declared to know the HPV, but 63.5% were unaware of the form of transmission and prevention and 89.7% were unaware of viral reactions in the body; 96.8% reported to have knowledge on CC, but 88.9% did not know how to associate it with HPV (França, França, & Moraes, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in the city of Teresina/PI with 126 women showed that 71.4% self-declared to know the HPV, but 63.5% were unaware of the form of transmission and prevention and 89.7% were unaware of viral reactions in the body; 96.8% reported to have knowledge on CC, but 88.9% did not know how to associate it with HPV (França, França, & Moraes, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out with women aged 18 to 50 years about knowledge on the Pap smear test showed that all the interviewed women claimed to know the test (Silva et al, 2015). However, a study carried out in the city of Teresina/PI showed that the women had insufficient knowledge about the significance of the test; the majority stated that they needed to take the test but they could not explain why they should do it (França, França, & Moraes, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Salientando as ideias de França et al, existe uma necessidade em programas de educação em saúde e de rastreamento precoce para que tenham sucesso, para isso, é necessário haver respostas mais efetivas da população de risco, assim como treinamento específico para os profissionais de saúde capaz de torná-los qualificados a fornecerem todas as informações a respeito do HPV, câncer do colo uterino entre outras DST's para depois realizar exames preventivos com as mulheres esclarecidas e acompanhamento adequado 13 .…”
Section: Quadrounclassified
“…Among the 189 types of viruses identified, it is reported that the human papillomavirus (HPV) has a numbered classification in the following order: virus of low oncogenic risk (6,11,30,42, 43 and 44) and those of high risk (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59 and 68). It should be noted that the oncogenic potential of this virus has a relation with the viral type, persistence and integration of the viral deoxyribonucleic acid and the host cell (2) .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cervical cancer, Latin America has one of the highest incidence rates in the world (5) . In Brazil, it is the third most common tumor in the female population (6) . The infection with the HPV virus is a high-risk one, from the Alphapapillomavirus type, and this factor leads to an unusual growth of cells located in the lower part of the uterus as well as the action of oncogenic proteins that cause cervical lesions (7) .…”
Section: Introductionmentioning
confidence: 99%